Evaluating the impact of a national brain health education course for older adults with intellectual and developmental disabilities and caregivers: Brain Health-IDD Program protocol - Mc Carron, Mary (My University, 2025)
Introduction: Adults with intellectual and/or developmental disabilities (IDD) experience higher rates of age-related health concerns, including dementia, than adults without disabilities. Despite this, current efforts to support brain health in ageing have often excluded this population. To address this gap, we will codesign, codeliver and evaluate a national virtual brain health education programme, Brain Health-IDD, for ageing individuals with IDD, family caregivers and health and social care providers. Methods and analysis: This study will evaluate the Brain Health-IDD Program, an interactive virtual psychoeducation course codesigned and coled by an interdisciplinary team of clinicians and people with lived experience. Three participant groups will be recruited from across Canada: adults with IDD, aged 40 years and older; family caregivers who have a family member with IDD aged 40 years and older or who are themselves aged 60 years and older; and health or social service providers who support adults with IDD aged 40 years and older. Outcomes will be measured at baseline, postcourse and 3-month follow-up. Data will be collected through structured surveys, including both closed and open-ended questions, and focus group interviews. Primary outcomes are participation, satisfaction and changes in knowledge and self-efficacy related to brain health among the three participant groups. Secondary outcomes for both adults with IDD and family caregivers include changes in health-related behaviours (social connections, sleep hygiene and physical activity), physical health, mental wellbeing, resilience and whether cognitive screening is initiated for adults with IDD and for caregivers. For health and social service providers, secondary outcomes include changes in brain health promotion practices and whether cognitive screening for older adults with IDD is initiated. Analysis of open-text survey responses and qualitative data from focus group interviews will explore the experiences of participants with the Brain Health-IDD Program. Ethics and dissemination: Institutional ethics approval was obtained from the Centre for Addiction and Mental Health Research Ethics Board. Programme findings and resources will be shared with advocacy groups, disability agencies, family caregiver organisations, clinicians and policymakers in the fields of disability, health and ageing at the provincial, national and international levels.
PUBLISHED